An Overview of the Reimbursement Decision-Making Processes in Bulgaria As a Reference Country for the Middle-Income European Countries - Kamusheva, Maria; Vassileva, Mariya; Savova, Alexandra; Manova, Manoela; Petrova, Guenka (Frontiers in Public Health, 2018)
Background: Policy makers face a lot of challenges in the process of drug reimbursement decision making, especially in the context of entering the market of more and more innovative medicinal products. The aim of the current study is to make an overview of the reimbursement system development and to evaluate the access of innovative medicines, which have entered the EU market in the period 2015-2017, in Bulgaria as a reference example for the middle-income European country. Methods: A literature and a legislative systematic review regarding the Bulgarian reimbursement system as well as a defining the number of available innovative reimbursed medicinal products in 2017 in Bulgaria was made. Results: The reimbursement legislation in Bulgaria is quite unstable due to constant changes, which have been made, especially in the recent years. Despite this fact, the reimbursement process in Bulgaria is in accordance with the Transparency Directive. Bulgarian patients have a relatively delayed access to innovative medicines as only 5% of centrally authorized MPs in 2017 are available in the positive drug list (PDL), 16% of all in 2016 and 18% - in 2015. This could be explained by the long procedure for their appraisal in Bulgaria: the first step is issuing an opinion by the HTA Committee, followed by negotiation of discounts between the marketing authorization holder and the National Health Insurance Fund (NHIF) and making a final decision by the National Council on Prices and Reimbursement (NCPR) for the inclusion into the Positive drug list. Conclusion: Optimization of the procedure for issuing reimbursement status for innovative medicinal products is needed such as improvements in the process of conducting HTA reports and their appraisal, incorporation of adequate systems for following the effectiveness and safety of MPs in the real-world conditions, value-based pricing implementation and increasing the financial control over the health insurance system. Key words: reimbursement, Bulgaria, low and middle-income Balkan countries, innovative medicines, access, affordability, positive drug list